A armadilha está pronta: Big Brother Brasil 21 e a espetacularização das relações étnico-raciais - Maciel, Dimitri José da Costa (Brasil, 2024)
This research was developed together with the Laboratory of Oral and Audiovisual History of Amazonas (LABHORA/AM) and aimed to problematize the proposal of black representation presented by TV Globo in Big Brother Brasil 21. Initially, priority was given to the production and systematization of files decoupage of the program's episodes available on Globoplay, and the analysis of the work carried out by the BBB 21 edition in the exhibition of conflicts, in the direction of events and in the transformation of participants into “heroes”, “villains” and “plants”. We also sought to understand the strategies developed by Lumena Aleluia, Gilberto Nogueira, João Luiz and Camilla de Lucas to try to survive the competition promoted by this reality show, according to studies that reflect on the format of this audiovisual product and the black presence on TV.